Strategi Inovasi Produk pada Usaha Batik Tanah Liek Bundo Kanduang - Indri Sefrina; Rose Rahmidani (Universitas Negeri Padang, 2018)
This reseachaims to analysze product’s innovation strategy at Batik Tanah Liek Bundo Kanduang. This reseach is a descriptive qualitative reseach. The data which are used in this reseach are primery and secondary data. The resources of the data are informen. The data of this reseach are collected by doing observation, interview and documentation. The data are analyzed qualitatively. The data of this research are validated by using source triangulation.The result of this research shows that Batik Tanah Liek Bundo Kanduang has not innovated all of their products attributes such as packaging, brand and guarantee. Batik Tanah Liek Bundo Kanduang has done innovation in term of motif and service. In the research the research find some obstacles at Batik Tanah Liek Bundo Kanduang. The obstacles are marketing, difficulties in finding raw materials, the lack of people’s knowledge about Batik Tanah Liek Bundo Kanduang difficulties in finding skillful employees in making batik, the uncompatible consumens demands and the lack of government’s attention.Keywords: Strategi, Innovation, Product, Batik Tanah Liek